2003
DOI: 10.1002/pca.682
|View full text |Cite
|
Sign up to set email alerts
|

The phytochemical profile and identification of main phenolic compounds from the leaf exudate of Aloe secundiflora by high‐performance liquid chromatography–mass spectroscopy

Abstract: The phytochemical profile of Aloe secundiflora (Aloeaceae) and the identity of eight major compounds, including the two main constituents, have been determined from the leaf exudate of this ethnoveterinary used species from Kenya and Tanzania. Analytical HPLC-MS studies of the exudate have revealed that it comprises a mixture of phenolic compounds, mainly anthrones (aloenin, aloenin B, isobarbaloin, barbaloin and other aloin derivatives), chromones and phenylpyrones with a low content of polysaccharides and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…10 It contains aloenin which has antiviral (Waihenya et al, 2005) and nematicidal activity against Ascaridia galli ( Kaingu et al, 2013) It contains anthrones (aloenin, isobarbaloin, aloenin B and barbaloin), chromones and phenylpyrones (Rebecca et al, 2003).…”
mentioning
confidence: 99%
“…10 It contains aloenin which has antiviral (Waihenya et al, 2005) and nematicidal activity against Ascaridia galli ( Kaingu et al, 2013) It contains anthrones (aloenin, isobarbaloin, aloenin B and barbaloin), chromones and phenylpyrones (Rebecca et al, 2003).…”
mentioning
confidence: 99%
“…For the determination of low levels of barbaloin in aloe-based products, chromatography/ mass spectrometry (LC/MS) and LC with diode array detection (DAD) in the UV range (LC/UV) were developed [31] . Analytical HPLC-MS method was developed and performed for the determination of barbaloin [32] . A rapid and sensitive fluorometric method is described for the determination of barbaloin in aloe vera gum, based on complexing europium with barbaloin in a micellar solution of CTAB (cetyl trimethylammonium bromide).…”
Section: Analytical Methods Of Barbaloinmentioning
confidence: 99%
“…The leaf exudate of this species has found ethno-veterinary use for treatment of bacterial diseases and parasites and in management of viral diseases. In poultry for example the exudates has been extensively used as prophylaxis for Newcastle diseas and as therapeutic for fowl typhoid, coccidiosis and other enteric conditions (Waihenya et al, 2003). Analytical High Performance Liquid Chromatography-Mass Spectropy (HPLC-MS) studies of the exudates have shown that it consists of a mixture of phenolic compounds or aliphatic compounds (Waihenya et al, 2003).…”
Section: Research Scholarshipmentioning
confidence: 99%
“…In poultry for example the exudates has been extensively used as prophylaxis for Newcastle diseas and as therapeutic for fowl typhoid, coccidiosis and other enteric conditions (Waihenya et al, 2003). Analytical High Performance Liquid Chromatography-Mass Spectropy (HPLC-MS) studies of the exudates have shown that it consists of a mixture of phenolic compounds or aliphatic compounds (Waihenya et al, 2003). This research was carried out to assess the anthelmintic activity of Aloe secundiflora extracts in vitro using the nematode parasite Ascaridia galli in larval development assays.…”
Section: Research Scholarshipmentioning
confidence: 99%